2021
DOI: 10.1038/s41577-021-00592-1
|View full text |Cite
|
Sign up to set email alerts
|

Progress of the COVID-19 vaccine effort: viruses, vaccines and variants versus efficacy, effectiveness and escape

Abstract: Where 2020 saw the development and testing of vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at an unprecedented pace, the first half of 2021 has seen vaccine rollout in many countries. In this Progress article, we provide a snapshot of ongoing vaccine efficacy studies, as well as real-world data on vaccine effectiveness and the impact of virus variants of concern. Where they have been deployed in a high proportion of the adult population, the currently approved vaccines have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
767
1
23

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 918 publications
(887 citation statements)
references
References 101 publications
5
767
1
23
Order By: Relevance
“…The effect of behaviour change on measured vaccine effectiveness is also suggested in another US study that found a drop in effectiveness over time only among people under 65 11. These examples show the fundamental challenges of assessing effectiveness against infection using routine surveillance data and highlight the need for systematic sampling, consideration of a comprehensive range of measured and unmeasured confounders, and careful interpretation 5…”
mentioning
confidence: 89%
See 3 more Smart Citations
“…The effect of behaviour change on measured vaccine effectiveness is also suggested in another US study that found a drop in effectiveness over time only among people under 65 11. These examples show the fundamental challenges of assessing effectiveness against infection using routine surveillance data and highlight the need for systematic sampling, consideration of a comprehensive range of measured and unmeasured confounders, and careful interpretation 5…”
mentioning
confidence: 89%
“…Since the initial randomised trials showed high efficacy of vaccines against a primary endpoint of symptomatic covid-19,1234 observational studies continue to evaluate and report real world performance of vaccines in different contexts and over time 56. In addition to providing direct protection against covid-19 disease, available vaccines also substantially reduce transmission, partly by protecting against both symptomatic and asymptomatic infection 7.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Post-introduction vaccine studies provide practitioners and policy makers with the kind of evidence that clinical trials cannot—including real world vaccine effectiveness against multiple clinical outcomes. Two linked studies12 that together examined three covid-19 vaccines, add to mounting evidence that efficacy reported in clinical trials translates well to the real world 34567. The studied vaccines—CoronaVac (Sinovac Biotech), BNT162b2 (Pfizer-BioNTech), and mRNA-1273 (Moderna)—performed well in preventing severe covid-19 and deaths in adults after two doses; a single dose was significantly less effective, and all three vaccines were effective (although demonstrably less so) against milder disease.…”
mentioning
confidence: 99%